Rights of an arrested person by virtue of section 28A of the criminal procedure code: an analysis / Nazlin Mohd Riduan…[et al.] - Mohd Riduan, Nazlin; Ishak, Nur Kartini; Rosly, Roshaira; Abd Malek, Zaid (Faculty of Law, 2013)
The amendment of section 28A of the Criminal Procedure Code (CPC) which came into force since September 2007, amplifies the rights of an arrested person which are the right to be informed on the grounds of arrest, the right to inform a relative or friend on the arrest and the right to consult with legal practitioner. However, there are certain criticisms brought forth on the enforcement of this amendment. Therefore, this study is carried out to provide a better understanding and to determine whether section 28A provides an even balance between the rights of persons arrested and the police's power and duty tin doing their job and to avoid unlawful arrest. Based on case laws and interviews that had been conducted, the result is as follows. The criticisms against section 28A and cases regarding infringement of arrested persons are more of an administrative and management issue rather than legal issues. Therefore, to conclude, it can be seen that section 28A itself is adequate to protect the rights of arrested persons. However, the powers conferred to the authorities should be monitored and the police officers themselves should be educated on how to execute their powers fairly and in accordance with the provision. It is hoped that the propose ideas stated will help in achieving the primary objective of section 28A of the CPC, which is to protect the rights of person arrested.